Critical appraisal of the views of healthcare professionals with respect to pharmacogenomics and personalized medicine in Greece. (January 2014) - Mai, Yuan; Mitropoulou, Christina; Papadopoulou, Xanthi E; Vozikis, Athanassios; Cooper, David N; van Schaik, Ron H; Patrinos, George P
Aim: In the postgenomic era, in many European countries, very little is known regarding the level of awareness of healthcare professionals with respect to pharmacogenomics and personalized medicine. Methods: Here, we report the findings of an in-depth study, involving 86 pharmacists and 208 physicians, to assess their level of awareness of pharmacogenomics and personalized medicine. Results: Our findings indicate that approximately 60% of pharmacists consider their level of knowledge of personalized medicine to be very low, while over half of the pharmacists and physicians intimate that they would be unable to explain the results of pharmacogenomic tests to their customers or patients, respectively. This situation may be directly related to the low level of their undergraduate education in genetics and pharmacogenomics. Conclusion: These findings provide the basis for assessing the views of healthcare professionals in relation to personalized medicine in Greece, and should help to facilitate the integration of genomics into the medical decision-making process.